2018
DOI: 10.3390/nano8040215
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Green Hydrothermal Synthesis of Few-Layer Graphene Oxide from Humic Acid

Abstract: The conventional synthesis route of graphene oxide (GOG), based on Hummers method, suffers from explosion risk, environmental concerns and a tedious synthesis process, which increases production costs and hinders its practical applications. Herein, we report a novel strategy for preparing few-layer graphene oxide (GOH) from humic acid via simple hydrothermal treatment. The formation of GOH is mainly attributed to the hydrolysis, oxidation and aromatization of humic acid under hydrothermal conditions. The as-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…In essence, HA is a mixture of many natural organic macromolecules consisting of alicyclic or aromatic skeleton units cross‐linked by carboxyl, hydroxyl, carbonyl, quinone, methoxyl and other oxygen‐containing functional groups . It owns diverse macromolecular structures with molecular weights ranging from 10 3 to 10 6 g mol −1 . HA exhibits strong coordination, exchange and adsorption actions with metal ions as strong binding energy always exists between them .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In essence, HA is a mixture of many natural organic macromolecules consisting of alicyclic or aromatic skeleton units cross‐linked by carboxyl, hydroxyl, carbonyl, quinone, methoxyl and other oxygen‐containing functional groups . It owns diverse macromolecular structures with molecular weights ranging from 10 3 to 10 6 g mol −1 . HA exhibits strong coordination, exchange and adsorption actions with metal ions as strong binding energy always exists between them .…”
Section: Introductionmentioning
confidence: 99%
“…Beall groups have reported that HA nanoparticles exhibit wrinkled sheet‐like shapes and have close particle size, thickness, C/O mass ratio and I G /I D (intensity ratio of significant G and D peaks in Raman spectrum) values to GO nanosheets, indicating that HA has similar physical and chemical structures, surface polarity and activity to GO. Hence, HA layers can be regarded as a natural GO . However, it is difficult to peel HA into layers because natural HA macromolecules are tightly stacked or agglomerated by van der waals force, hydrogen bond and π‐π interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra show two main peaks at around 1360 cm −1 and 1590 cm −1 signifying the D‐band and the G‐band, respectively. The I D /I G ratio gauges the extent of defects in the graphitic lattice and the size of the sp 2 hybridized carbon domains present and is reported in Table S1. As the exfoliation potential is increased, the I D /I G ratio increases due to the stronger oxidative conditions present on the graphitic lattice.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrothermal treatment is a thermo-chemical conversion technique resulting in efficient hydrolysis and pyrolysis with high temperature and high pressure [36,37]. During the hydrothermal process, the original layered structural materials can be exfoliated into few-layer materials by thermo-chemical intercalation, which provides an important method for the preparation of low-dimensional materials [36][37][38][39][40]. In 2014, Liu et al proposed that single-or few-layer graphene is produced by hydrothermal exfoliation of graphite [41].…”
Section: Introductionmentioning
confidence: 99%